2005
DOI: 10.1103/physreve.72.056710
|View full text |Cite
|
Sign up to set email alerts
|

Fast flat-histogram method for generalized spin models

Abstract: We present a Monte Carlo method that efficiently computes the density of states for spin models having any number of interaction per spin. By combining a random-walk in the energy space with collective updates controlled by the microcanonical temperature, our method yields dynamic exponents close to their ideal random-walk values, reduced equilibrium times, and very low statistical error in the density of states. The method can host any density of states estimation scheme, including the Wang-Landau algorithm a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 73 publications
1
18
0
Order By: Relevance
“…so that the results no longer depend on the normalization of the wave function. The periodicity of the expression (52) shows that both m x and m y take integer values from 0 to N − 1. Thus…”
Section: A Density-density Correlations: the Function ∆mentioning
confidence: 99%
See 2 more Smart Citations
“…so that the results no longer depend on the normalization of the wave function. The periodicity of the expression (52) shows that both m x and m y take integer values from 0 to N − 1. Thus…”
Section: A Density-density Correlations: the Function ∆mentioning
confidence: 99%
“…There are various refinements one can make to this process 45,[52][53][54][55][56] . In general, it has been shown that more complex patterns of choosing f can lead to faster convergence.…”
Section: A Wang-landaumentioning
confidence: 99%
See 1 more Smart Citation
“…In statistical physics, the Fast Flat Histogram method [9] employing Wang Landau algorithm [10,11] was introduced to estimate the density of states g(E), i.e., the number of all possible states for an energy level E of the system. The algorithm is based on the observation that if a random walk in energy space is performed by flipping spins randomly for a spin system and the probability to visit a given energy level E is proportional to the reciprocal of the density of states 1/g(E), then a flat histogram is generated for the energy distribution.…”
Section: Rationalementioning
confidence: 99%
“…Several proposals have been presented to generalize cluster update approaches in multicanonical ensemble simulations, either using spin-bond representations of the partition function, [24,25,26,27], or cluster building algorithms based on alternative ways of computing the microcanonical temperature, β(E) [28,29].…”
Section: Cluster Dynamicsmentioning
confidence: 99%